1973
DOI: 10.1159/000180182
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcaemia and Bone Disease in Renal Failure

Abstract: Various aspects of calcium and bone metabolism were studied in 50 cases of chronic renal failure. It was found that elevation of plasma alkaline phosphatase was generally associated with reduced metacarpal cortical thickness and in a small number of biopsies reflected the osteomalacic rather than the resorptive component of renal bone disease. Patients with an elevated plasma alkaline phosphatase tended to have a lower plasma calcium, lower plasma bicarbonate and lower radiocalcium absorption than patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…It has previously been shown that metabolic acidosis reduces the intestinal absorption of calcium [4,9,11], and also that it produces an increased urine calcium [18] by reducing tubular calcium reabsorption [8,19]. The results reported in this paper agree entirely with these earlier findings but extend the known effects of acidosis to include an action on bone turnover.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It has previously been shown that metabolic acidosis reduces the intestinal absorption of calcium [4,9,11], and also that it produces an increased urine calcium [18] by reducing tubular calcium reabsorption [8,19]. The results reported in this paper agree entirely with these earlier findings but extend the known effects of acidosis to include an action on bone turnover.…”
Section: Discussionsupporting
confidence: 88%
“…The relation between calcium uptake by the vesicles and pH is strikingly similar to the variation of alkaline phosphatase activity with pH, and the matrix vesicles contain this enzyme in large quantities [26]. Moreover, alkaline phosphatase is a function of the forming, but not resorbing bone surfaces [9], Holdsworth [27] and Russell el al. [28] have made the interesting suggestion that calcium ATPase in the intestine may be an alkaline phosphatase, and if this is the case at other sites of calcium transport then it would provide a simple explanation for the inhibitory affects of acidosis that we have observed.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations